Classical anticytokinins do not interact with cytokinin receptors but inhibit cyclin-dependent kinases - Spíchal, Lukás; Krystof, Vladimír; Paprskárová, Martina; Lenobel, René; Styskala, Jakub; Binarová, Pavla; Cenklová, Vera; De Veylder, Lieven; Inzé, Dirk; Kontopidis, George; Fischer, Peter M; Schmülling, Thomas; et al. (The Journal of biological chemistry, 2007)
Cytokinins are a class of plant hormones that regulate the cell cycle and diverse developmental and physiological processes. Several compounds have been identified that antagonize the effects of cytokinins. Based on structural similarities and competitive inhibition, it has been assumed that these anticytokinins act through a common cellular target, namely the cytokinin receptor. Here, we examined directly the possibility that various representative classical anticytokinins inhibit the Arabidopsis cytokinin receptors CRE1/AHK4 (cytokinin response 1/Arabidopsis histidine kinase 4) and AHK3 (Arabidopsis histidine kinase 3). We show that pyrrolo[2,3-d]pyrimidine and pyrazolo[4,3-d]pyrimidine anticytokinins do not act as competitors of cytokinins at the receptor level. Flow cytometry and microscopic analyses revealed that anticytokinins inhibit the cell cycle and cause disorganization of the microtubular cytoskeleton and apoptosis. This is consistent with the hypothesis that they inhibit regulatory cyclin-dependent kinase (CDK) enzymes. Biochemical studies demonstrated inhibition by selected anti-cytokinins of both Arabidopsis and human CDKs. X-ray determination of the crystal structure of a human CDK2-anticytokinin complex demonstrated that the antagonist occupies the ATP-binding site of CDK2. Finally, treatment of human cancer cell lines with anticytokinins demonstrated their ability to kill human cells with similar effectiveness as known CDK inhibitors.
Keywords: Cyclin-Dependent Kinase 2; buněčný cyklus; Gene Expression Regulation, Plant; nádory kostí; krystalografie rentgenová; cytoskelet; proliferace buněk; Crystallography, X-Ray; Arabidopsis; Apoptosis; průtoková cytometrie; Cell Cycle; Humans; nádory prsu; transportní proteiny; proteiny huseníčku; cyklin-dependentní kinasa 2; Tumor Cells, Cultured; lidé; nádorové buňky kultivované; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; cytokininy; receptory buněčného povrchu; Cell Proliferation; Cytokinins; osteosarkom; Flow Cytometry; Pyrimidines; Cytoskeleton; Breast Neoplasms; proteinkinasy; regulace genové exprese u rostlin; apoptóza; Carrier Proteins; Osteosarcoma; Histidine Kinase; Arabidopsis Proteins; chronická myeloidní leukemie; Receptors, Cell Surface; Bone Neoplasms; histidinkinasa; Protein Kinases; pyrimidiny